2012
DOI: 10.1128/jcm.00767-12
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Diversity in the Bronchial Tracts of Patients with Chronic Obstructive Pulmonary Disease

Abstract: i Culture of bacteria from bronchial secretions in respiratory patients has low sensitivity and does not allow for complete assessment of microbial diversity across different bronchial compartments. In addition, a significant number of clinical studies are based on sputum samples, and it is not known to what extent they describe the real diversity of the mucosa. In order to identify previously unrecognized lower airway bacteria and to investigate the complexity and distribution of microbiota in patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(156 citation statements)
references
References 43 publications
(49 reference statements)
5
146
2
3
Order By: Relevance
“…Sputum microbiota was demonstrated to be not concordant to microbes in the lung (13,14), and lung tissue could be collected only when lung transplantation will be conducted (3). This drove BALF sampling to be preferable strategy, in evaluating lung microbiota and corresponding involvement in lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Sputum microbiota was demonstrated to be not concordant to microbes in the lung (13,14), and lung tissue could be collected only when lung transplantation will be conducted (3). This drove BALF sampling to be preferable strategy, in evaluating lung microbiota and corresponding involvement in lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Prior approaches to bacterial identification by DNA sequencing have included fluorescent Sanger sequencing of hundreds of small variable regions of 16S ribosomal amplimer clones (19,20), length heterogeneity (LH) PCR for 16S ribosomal variable regions (21), restriction fragment polymorphisms in 16S (19,21), arrays with bacterium-specific probes, such as PhyloChip (22,23), and early applications of NGS (24,25). These methods have been applied to various clinical situations, such as the microbiome of suboptimally controlled asthma (22), cystic fibrosis (19,21), chronic obstructive pulmonary disease (COPD) (24,26,27), bronchiectasis (28), pleurisy (20), forensic assessment of drowning (25), and intubated patients (23). These studies have revealed unexpectedly large numbers of bacterial genera in patients with clinical illnesses and in healthy individuals (29,30).…”
mentioning
confidence: 99%
“…Streptococcus pneumoniae -один из наиболее часто вы-являемых микроорганизмов, идентифицируемых в дыха-тельных путях пациентов с ХОБЛ даже в стабильный пе-риод без эпизодов обострений и антибиотикотерапии за предшествующие 12 мес [1]. D. Garcha и соавт.…”
Section: контактная информацияunclassified